Supply chain management in the digital advertising industry of Bangladesh: a case study of Spade Digital - Osman, Mohammad Newaz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.